2022
DOI: 10.1111/sode.12630
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perceptions of social risk and prosocial tendencies: Developmental change and individual differences

Abstract: Many prosocial behaviors involve social risks such as speaking out against a popular opinion, bias, group norm, or authority. However, little is known about whether adolescents’ prosocial tendencies develop over time with their perceptions of social risks. This accelerated longitudinal study used within‐subject growth‐curve analyses to test the link between adolescents' prosocial tendencies and social risk perceptions. Adolescents completed self‐reports annually for 3 years (N = 893; Mage = 12.30 years, 10–14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…This effect was moderated by social craving, such that only when adolescents were strongly motivated by a craving for social connection throughout the day did they show this link between risk‐taking and prosocial behavior. Our study extends prior research, which demonstrated that risk‐taking and prosocial behavior converge from early‐ to late‐adolescence (Armstrong‐Carter, Do, Duell, et al., 2021), and were positively correlated (Blankenstein et al., 2020). Specifically, our study builds on this work by revealing that risk‐taking and prosocial behavior co‐occur on a smaller time scale, within days.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This effect was moderated by social craving, such that only when adolescents were strongly motivated by a craving for social connection throughout the day did they show this link between risk‐taking and prosocial behavior. Our study extends prior research, which demonstrated that risk‐taking and prosocial behavior converge from early‐ to late‐adolescence (Armstrong‐Carter, Do, Duell, et al., 2021), and were positively correlated (Blankenstein et al., 2020). Specifically, our study builds on this work by revealing that risk‐taking and prosocial behavior co‐occur on a smaller time scale, within days.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, our findings should be replicated in other samples to clarify generalizability across contexts, and examine individual differences by gender, age, ethnicity, and socioeconomic status. For example, it is possible that risk-taking is positively related to prosocial behavior among older adolescents (around age 15-17), as prior research has suggested (Armstrong-Carter, Do, Duell, et al, 2021), but not among younger adolescents (age 14 and below). In particular, relatively older adolescents' increased perspective taking and self-regulation skills may enable them to more effectively weigh risks, make calculated choices, and engage in empathic but risky actions.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
See 3 more Smart Citations